I have a feeling your question is
x/(x-2) - (x+2)/x
Factoring doesn't make much sense, more than likely it says "simplify", am I right?
for (3 + √5)(3 - √5)
You should recognize the 'difference of squares' patter, or you could just expand it
= 9 - 5 = 4
4 is the only answer
How to factor (x/x-2)-(x+2/x)
my answer is -x^2-x-2/x
and (3+sq rt 5)*(3-sq rt 5)
my answers are either 4 or 3*sq rt 5^2
are any of these right?
Thanks so much for all of your help.
5 answers
Yes, you are right. It does say simplify.
back to x/(x-2) - (x+2)/x then
common denominator is x(x-2)
so x/(x-2) - (x+2)/x
= [x^2 - (x+2)(x-2)] / [x(x-2)]
= (x^2 - x^2 + 4)/[x(x-2)]
= 4/(x(x-2))
common denominator is x(x-2)
so x/(x-2) - (x+2)/x
= [x^2 - (x+2)(x-2)] / [x(x-2)]
= (x^2 - x^2 + 4)/[x(x-2)]
= 4/(x(x-2))
I changed my answer to
x/(x-2) - (x+2)/x to 4/x(x-2)
Is that right?
x/(x-2) - (x+2)/x to 4/x(x-2)
Is that right?
got it, thanks!